Perlindungan Hukum Bagi Pekerja Anak: Tinjauan Perspektif Keadilan dan Kesejahteraan Anak - Meirina Nurlani (Jurnal Kajian Pembaruan Hukum, 2021)
Increasing economic demands shape the situation of a child having to work to help his parents to support his family's economy. Therefore, it is necessary to provide legal protection for child labor. Legal protection for child labor is an important instrument that must be considered by the government; considering that the guarantee of legal protection is a moral responsibility for the government to fulfill the welfare and justice of child workers. This type of research is legal research. This legal research uses a statute approach and conceptual approach. The legal materials used in this legal research are primary and secondary legal materials. The results of this study state that legal protection for child labor is based on various laws and regulations. The welfare of child workers will be obtained when the rights of child workers as stated in various laws and regulations are fulfilled and guaranteed by the company. Prosperity in this study does not only have material meaning, but includes non-material aspects; as well as continuing to provide flexibility for children to continue to develop their capacity. Furthermore, regarding justice, child workers should also be given legal protection; considering that children are human beings who have human rights. Tackling the problem of child labor can be done using three efforts; namely preventive efforts, curative efforts, and repressive measures. On the other hand, an integrated planning is needed to deal with the problem of child labor. This sustainable planning is carried out to fulfill various fundamental rights of child labor. KEYWORDS: Child Workers, Child Rights, Legal Protection for Child Workers.